2022
DOI: 10.1002/ijch.202100112
|View full text |Cite
|
Sign up to set email alerts
|

Indium Selenide (In2Se3) – An Emerging Van‐der‐Waals Material for Photodetection and Non‐Volatile Memory Applications

Abstract: The search for ultrathin and robust ferroelectrics leads to few promising two-dimensional (2D) materials. In 2 Se 3 has drawn special attention owing to the existence of intercoupled in-plane (IP) and out-of-plane (OOP) ferroelectricity in monolayer form, which makes it a potential candidate for emerging artificial intelligence, information processing and memory applications. In addition, the high optical absorption and phase-dependent visible to infrared bandgap become advantageous from optoelectronics point-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 149 publications
(413 reference statements)
0
14
0
Order By: Relevance
“…When the α-In 2 Se 3 constructs a heterojunction with n-Si, the charge distribution will be reconstructed to ensure the dynamic balance of diffusion carriers at the interface of this junction until the Fermi levels are aligned. The electric field of the junction interface can be enhanced or inhibited by the α-In 2 Se 3 ferroelectric field, leading to the accumulation or depletion of carriers . It also means that the barrier height (Φ) across the junction and electromotive force (EMF) with illumination can be modulated by the ferroelectric remanent polarization field after reconstruction as illustrated in Figure e .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the α-In 2 Se 3 constructs a heterojunction with n-Si, the charge distribution will be reconstructed to ensure the dynamic balance of diffusion carriers at the interface of this junction until the Fermi levels are aligned. The electric field of the junction interface can be enhanced or inhibited by the α-In 2 Se 3 ferroelectric field, leading to the accumulation or depletion of carriers . It also means that the barrier height (Φ) across the junction and electromotive force (EMF) with illumination can be modulated by the ferroelectric remanent polarization field after reconstruction as illustrated in Figure e .…”
Section: Resultsmentioning
confidence: 99%
“…The electric field of the junction interface can be enhanced or inhibited by the α-In 2 Se 3 ferroelectric field, leading to the accumulation or depletion of carriers. 55 It also means that the barrier height (Φ) across the junction and electromotive force (EMF) with illumination can be modulated by the ferroelectric remanent polarization field after reconstruction as illustrated in Figure 6 e. 11 Consequently, the energy levels near the Si surface bent upward, and the energy levels near the α-In 2 Se 3 surface are bent downward, leading to the formation of a built-in electric field at the α-In 2 Se 3 /n-Si interface. The electrons and holes are then rapidly separated by the built-in electric field and collected by the respective electrodes, ultimately generating the photocurrent ( Figure 6 f).…”
Section: Resultsmentioning
confidence: 99%
“…Since the discovery of ferroelectricity in 2D α-In 2 Se 3 , plenty of experimental and theoretical works have been devoted to exploring its application in non-volatile memories [25][26][27][28][29][30][31][32][33][34] . Wan et al demonstrated a ferroelectric field-effect transistor (FeFET) using ultrathin α-In 2 Se 3 as a non-volatile ferroelectric gate and graphene as a conducting channel, which were separated by an insulating hexagonal boron nitride layer 35 .…”
Section: Introductionmentioning
confidence: 99%
“…Among 2D ferroelectrics that are characterized by the presence of exclusively out-of-plane (OOP) or in-plane (IP) polarization such as in CuInP 2 S 6 , 1T-WTe 2 , SnTe, etc., In 2 Se 3 has drawn special attention owing to the existence of stable intercoupled IP and OOP ferroelectricity down to the monolayer limit. The origin of the ferroelectricity in α-In 2 Se 3 arises from the relative displacement of the central Se atomic layer with respect to the adjacent In atomic layers, which breaks the centrosymmetry in the crystal and results in two energetically degenerate polarization states . This unique character makes In 2 Se 3 a potential candidate for emerging artificial intelligence, information processing, and memory applications.…”
Section: Introductionmentioning
confidence: 99%